Insecticide seed treatments for managing maggots (Diptera: Anthomyiidae) in onion across selected regions in North America - Leonardo D. Salgado; Alan G. Taylor; Mary Ruth McDonald; Rob G. Wilson; Timothy D. Waters; Josephine B. Antwi; Stuart Reitz; Nathan Hesler; Brian A. Nault (Crop Protection, 2026)

Attractiveness of citronellol identified from Rosa chinensis volatiles to the thrips pest Frankliniella occidentalis and its beneficial effect on population development - Guang Zeng; Yuping Yang; Filippo Maggi; Feiyu Jiang; Rongrong Yuan; Ling Chen; Yulin Gao; Yu Cao; Kaixian Wu; Stuart R. Reitz (Journal of Pest Science, 2025)

Reproductive disruption induced by Beauveria bassiana in Frankliniella occidentalis as a potential long-term biocontrol strategy - Qikai Zhang; Dengjie Wang; Sheng Liu; Stuart Reitz; Haihong Wang; Baoqian Lyu (Pesticide Biochemistry and Physiology, 2025)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

Elevated CO2 affects interspecific competition between the invasive thrips Frankliniella occidentalis and native thrips species - Ting Zhang; Chun Wang; Feiyu Jiang; Min Li; Ling Chen; Hua Xie; Lijuan Wang; Yulin Gao; Stuart R. Reitz; Yu Cao (Journal of Pest Science, 2024)

Correction to: Host preference of Thrips hawaiiensis for different ornamental plants - Yu Cao; Stuart R. Reitz; Giacinto Salvatore Germinara; Chun Wang; ·Lijuan Wang; Siyu Yang; Yulin Gao; Wenqing Zhang; Can Li (Journal of Pest Science, 2022)

Host preference of Thrips hawaiiensis for different ornamental plants - Yu Cao; Stuart R. Reitz; Giacinto Salvatore Germinara; Chun Wang; Lijuan Wang; Siyu Yang; Yulin Gao; Wenqing Zhang; Can Li (Journal of Pest Science, 2022)
Thrips hawaiiensis is a common thrips pest that damages the flowers of various plants. The differing population sizes of T. hawaiiensis among host plants suggest its preference and performance vary among host plants. In this study, the host fitness of T. hawaiiensis for different flowers was assessed through field investigation. The behavioral responses of T. hawaiiensis to the color and volatiles of flowers eliciting different apparent fitness levels and their development and survival on the plants were also studied. Adults and larvae of T. hawaiiensis were found in the flowers of 21 species, which were classified into four fitness levels for this thrips species. T. hawaiiensis showed significantly different visual responses to the color and olfactory responses to the volatiles of four tested flowers (each representing one of the four fitness levels), with the rankings of visual preferences for Dianthus caryophyllus > Tulipa gesneriana > Hydrangea macrophylla > Rosa rugosa , and olfactory preferences for H. macrophylla ≥ T. gesneriana > D. caryophyllus > R. rugosa . Plant species had significant influences on the development and survival of T. hawaiiensis , with developmental times from egg to adult of 9.58 d, 9.92 d, 10.35 d and 10.75 d on H. macrophylla , T. gesneriana , D. caryophyllus and R. rugosa , respectively, and corresponding survival rates of 76.33%, 71.33%, 64.00% and 59.00%. In summary, this study shows that olfactory preferences were consistent with the field performance of T. hawaiiensis on the four flower plants tested. Further, fitness levels of host plant flowers are correlated with development rate and survivorship of T. hawaiiensis . Our study adds to the understanding of the mechanism of host selection by thrips and provides basic information to underpin the management of T. hawaiiensis on horticultural plants.

Special issue on novel management tactics for the Western flower thrips - Yulin Gao; Stuart R. Reitz (Journal of Pest Science, 2021)

Simultaneous application of entomopathogenic Beauveria bassiana granules and predatory mites Stratiolaelaps scimitus for control of western flower thrips, Frankliniella occidentalis - Xingrui Zhang; Shengyong Wu; Stuart R. Reitz; Yulin Gao (Journal of Pest Science, 2021)

Life history traits of Blaptostethus pallescens (Hemiptera: Anthocoridae), a candidate for use in augmentative biological control in Egypt - Islam S. Sobhy; Amany M. Abdul-Hamid; Awad A. Sarhan; Ahmed A. Shoukry; Nasser S. Mandour; Stuart R. Reitz (Applied Entomology and Zoology, 2014)

Development, consumption rates and reproductive biology of Orius albidipennis reared on various prey - Islam S. Sobhy; Awad A. Sarhan; Ahmed A. Shoukry; Gamal A. El-Kady; Nasser S. Mandour; Stuart R. Reitz (BioControl, 2010)